Study on rheological parameters of interfacial adsorption layers of ethoxylated water-insoluble surfactants - I. А. Gritskova; E. V. Milushkova; S. M. Levachev; Yu. N. Malakhova; E. M. Teleshov; D. A. Levanova (Тонкие химические технологии, 2015)
The article presents the results of a study on the behavior of water-insoluble ethoxylated surfactants of different nature on the phase boundary by the method of oscillating drops and by the method of Langmuir-Blodgett films. It was shown that the water-insoluble ethoxylated surfactants form supramolecular structures and stable layers at the water/air interface.